Efforts to Improve Aqidah Akhlak Learning Outcomes Through the Discussion Method for MA Nuriddahlani Probolinggo Students - Devy Habibi Muhammad; Robiatul Adawiyah (al-Afkar, Journal For Islamic Studies, 2023)
In the learning process using discussion methods, educators must provide the best activities in the learning process and provide opportunities to students so that students can actively participate in learning that uses discussion methods so that they can exchange opinions so that they can affect learning and effective results. The formulation of this research problem is "Can the discussion method improve the learning outcomes of class XI students in the subjects of Aqidah Akhlak in MA Nuriddahlani Probolinggo?". The research method used is the method of class action, research that is carried out by studying the problems that occur by performing organized and planned actions and analyzing from each influence and action with the aim to overcome the problem that occurs. The results showed that the method of discussion in learning ahlaq the learners of each cycle with a pre-cycle level of completion of student learning 35.71% rose to 19 students or 67.85% increased, in cycle II to 28 students or 100%. This means the discussion methods used in learning successfully improve students' learning achievement.